2020
DOI: 10.1186/s13756-019-0660-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of patients with pneumonia caused by Klebsiella pneumoniae in Taiwan and prevalence of antimicrobial-resistant and hypervirulent strains: a retrospective study

Abstract: Background: We aimed to compare the clinical characteristics of patients with community-acquired pneumonia (CAP), healthcare-associated pneumonia (HCAP), and hospital-acquired pneumonia (HAP) caused by Klebsiella pneumoniae and analyze the antimicrobial resistance and proportion of hypervirluent strains of the microbial isolates. Methods: We conducted a retrospective study on patients with pneumonia caused by K. pneumoniae at the Taipei Veterans General Hospital in Taiwan between January 2014 and December 2016… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…In this study, K. pneumoniae was isolated from 9% of diseased chickens and 16.7% of environment samples, which is inconsistent with the findings reported in a previous study in Egypt, where K. pneumoniae was recovered from 35% of broiler chickens and 25% of water samples [ 42 ]. However, the prevalence of K. pneumoniae among contact poultry workers (22.7%) and hospitalized patients (14.4%) in the same region was lower than lately published reports in Egypt [ 7 , 42 , 43 ] or abroad, both in China [ 44 ] and Taiwan [ 45 ]. Hence, the direct transmission may be facilitated via close contact between chickens and humans as evidenced previously by Davis et al [ 46 ].…”
Section: Discussionmentioning
confidence: 63%
“…In this study, K. pneumoniae was isolated from 9% of diseased chickens and 16.7% of environment samples, which is inconsistent with the findings reported in a previous study in Egypt, where K. pneumoniae was recovered from 35% of broiler chickens and 25% of water samples [ 42 ]. However, the prevalence of K. pneumoniae among contact poultry workers (22.7%) and hospitalized patients (14.4%) in the same region was lower than lately published reports in Egypt [ 7 , 42 , 43 ] or abroad, both in China [ 44 ] and Taiwan [ 45 ]. Hence, the direct transmission may be facilitated via close contact between chickens and humans as evidenced previously by Davis et al [ 46 ].…”
Section: Discussionmentioning
confidence: 63%
“…A more recent report by Harada et al demonstrated that more than half of hvKp infections from seven different hospitals in Japan were healthcare-associated or nosocomial [ 31 ]. Additionally, Chih-Han Juan, et al reported that hvKp were prevalent in community-acquired, healthcare-associated and hospital-acquired pneumonia patients [ 32 ]. These data are consistent with our findings that hvKp appears to be infiltrating into our healthcare systems.…”
Section: Discussionmentioning
confidence: 99%
“…11 A recent study that assessed CAP due to K. pneumoniae (isolated HV-KP accounted for 54 of 68 patients; 79.4%) also reported chronic kidney disease (66.2%) and malignancy (38.2%) as being common co-morbidities. 14 However, the present case was not complicated by other conditions, and the patient was an elderly woman, suggesting that the HV-KP strain causing CAP might have different clinical characteristics from those of the typical HV-KP strain that causes liver abscess, meningitis, and endophthalmitis. 2 In this case, the patient had bacteremia in addition to septic shock and respiratory failure in the initial presentation.…”
Section: Discussionmentioning
confidence: 67%
“…The Characteristics of Nine Adult Cases with Community-Acquired Pneumonia Due to Hypervirulent Klebsiella pneumoniae Including the Present Case[14][15][16] …”
mentioning
confidence: 97%